La intervención de trabajador social en los casos de mujeres víctimas de violencia en el barrio Florida Sector 6 - Farfán Gonzales, Joselyn Daniela (Machala : Universidad Técnica de Machala, 2022)
This systematization work will be based on gender violence, and how this has caused great physical, sexual, and psychological damage to the women of the Florida Seis sector. On the other hand, this project will focus on the social worker’s intervention as he acts in this field through advice, group work as in policy guidance and analysis. Chapter two talks about the methodologies that will be used in this project, namely, the qualitative and the quantitative methods. The qualitative methodology is based on collecting the necessary information to understand and learn about a phenomenon or problem; while the quantitative methodology is based on studying and collecting data that has already been analyzed and investigated. This way, it will be possible to perform a social diagnosis, analyze the problem in the Florida Seis neighborhood, and meet the women who are victims of violence. With these techniques, it will be possible to review and come up with an action plan with certain activities that will help us eradicate this problem. All the activities that were performed helped to promote participation through workshops, conferences, and talks. This also helped the women understand where to go in cases of violence and how professionals can help them in exercising their rights as human beings.
El presente trabajo de sistematización se basa en la violencia de género, y como esta ha provocado grandes daños físicos, sexuales y psicológicos a las mujeres del sector Florida seis. Por otro lado, este proyecto tiene la necesidad de enfocarse en la intervención del trabajador social como actúa en este campo por medio de asesoramientos, trabajo en grupos como en la orientación de políticas y análisis. En el capítulo dos, se habla de la metodología a emplear en este proyecto, por un lado, está la metodología cualitativa que se basa en recoger información necesaria para construir y conocer acerca de un fenómeno o problema; mientras que la metodología cuantitativa se basa en estudiar y recopilar datos ya analizados e investigados. De esa manera, se puede dar paso a realizar el diagnóstico social, luego analizar la problemática en el barrio Florida sector seis y conocer las mujeres que son víctimas de violencia se pudo revisar y realizar un plan de acción con determinadas actividades que nos ayudarán a radicar esta problemática. Todas las actividades ejecutadas ayudaron a promover la participación por medio de talleres, conferencias, charlas que es muy caro el proceso de dónde acudir en casos de violencia y qué profesionales puede ayudarles y ejercer sus derechos como seres humanos.
Keywords: VIOLENCIA; GENERO; INTERVENCION; PARTICIPACION